Film and method for producing film
Patent Information
- Application Number
- JP2021058195
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-03-30
AI Technical Summary
【0009】 本発明によれば、耐破袋性を有すると共に易カット性に比較的優れたフィルムを提供すること、および、斯かるフィルムの製造方法を提供することができる。
Smart Images

Figure 0007637550000001 
Figure 0007637550000002 
Figure 0007637550000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a film and a method for making the film. [Background technology]
[0002] Films containing at least two kinds of olefin-based polymers are used in various applications. For example, such films may be used as a sealant layer of a multilayer film used as a packaging material. A multilayer film having such a sealant layer can be formed into a packaging bag by heat sealing the sealant layer on the inside to form a storage space. An article can be stored in the packaging bag and sealed to form a package.
[0003] The above-mentioned packaging bag is required to be easily torn by hand when removing an article from the package (easy cut property), and to form a package that is not easily broken when dropped (bag breakage resistance). For this reason, the film used as the sealant layer is also required to be easy to cut and rupture-resistant. As a film that can impart such easy-to-cut property and rupture-resistant property to the packaging bag, Patent Document 1 discloses a film that contains two types of propylene-based polymers, an ethylene-based polymer, and a specified crystal nucleating agent in a specified ratio. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-172780 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, even for the above-mentioned films, there is still room for improvement in terms of ease of cutting, and there is a demand for films having even better ease of cutting.
[0006] Therefore, an object of the present invention is to provide a film that has resistance to bag breakage and is relatively easy to cut, and to provide a method for producing such a film. [Means for solving the problem]
[0007] The film according to the present invention is A film containing at least two kinds of olefin polymers, the at least two kinds of olefin polymers form an islands-in-a-sea type phase-separated structure consisting of a continuous phase and a discontinuous phase, The degree of orientation in the MD direction of the film determined by wide-angle X-ray scattering measurement is 76% or more.
[0008] The method for producing a film according to the present invention comprises the steps of: A method for producing the above film, comprising the steps of: A melt-kneading step of melt-kneading a mixture containing at least two kinds of propylene-based polymers, an ethylene-based polymer, and a phosphate metal salt-based nucleating agent; an extrusion step of extruding the kneaded material obtained in the melt kneading step into a sheet shape; a cooling step in which the sheet-like kneaded material obtained in the extrusion step is pressed against a cooling roll by gas blown out of an air chamber to cool it; and forming a film by forming the sheet-like kneaded material into a film. In the cooling process, the amount of gas blown out from the air chamber is adjusted so that the gas pressure in the air chamber is 50 Pa to 300 Pa. Effect of the Invention
[0009] According to the present invention, it is possible to provide a film that has resistance to bag tearing and is relatively easy to cut, and to provide a method for producing such a film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The film according to the present embodiment contains at least two kinds of olefin polymers, which form an islands-in-a-sea type phase-separated structure consisting of a continuous phase and a discontinuous phase in the film.
[0011] In addition, the film according to this embodiment has an orientation degree in the MD direction (the flow direction of the film during film formation) of the film determined by wide-angle X-ray scattering measurement of 76% or more, preferably 76% to 98%, and more preferably 76% to 95%. The orientation degree in the MD direction can be determined by the method described in the Examples below. In addition, the orientation degree in the MD direction can be changed by adjusting the gas pressure in the air chamber and adjusting the force pressing the sheet-like kneaded material against the cooling roll in the film production method described below. Specifically, the orientation degree in the MD direction can be increased by decreasing the gas pressure in the air chamber, and can be decreased by increasing the gas pressure.
[0012] Furthermore, the film according to the present embodiment preferably satisfies the following formulas (1) and (2). Nx, Ny, Nz, and θ in the following formulas (1) and (2) can be determined by the method described in the Examples below. In addition, Nx, Ny, Nz, and θ can be changed by adjusting the gas pressure in the air chamber and adjusting the force pressing the sheet-like kneaded material against the cooling roll in the film manufacturing method described below. Specifically, by lowering the gas pressure in the air chamber, Nx can be increased and Ny and Nz can be decreased, and by increasing the gas pressure, Nx can be decreased and Ny and Nz can be increased. (Nx×cosθ-Ny×cosθ) / d≧3.0×10 -8 (1) (Nx-(Ny+Nz) / 2) / d≧3.4×10 -8 (2) (In the formula, Nx represents the refractive index of the slow axis of the film determined by three-dimensional refractive index measurement. Ny represents the refractive index of the fast axis of the film determined by three-dimensional refractive index measurement. Nz indicates the refractive index in the thickness direction of the film determined by three-dimensional refractive index measurement. θ indicates the angle (°) between the MD direction of the film and the slow axis, which is determined by three-dimensional refractive index measurement. d indicates the film thickness (nm).
[0013] As the olefin polymer, for example, a propylene polymer can be used. The propylene polymer is a polymer containing 50% by mass or more (preferably more than 50% by mass) of monomer units derived from propylene, and may be a propylene homopolymer or a propylene copolymer.
[0014] Such a propylene-based polymer may be a propylene-based polymer A-1 containing preferably 95% by mass or more of monomer units derived from propylene. The propylene-based polymer A-1 may contain more preferably 97% by mass or more, and even more preferably more than 99% by mass of monomer units derived from propylene. Such a propylene-based polymer A-1 may be a propylene homopolymer or a propylene-based copolymer.
[0015] When the propylene polymer A-1 is a propylene copolymer, the propylene polymer A-1 may contain, in addition to the monomer units derived from propylene, monomer units derived from ethylene and / or an α-olefin having 4 to 12 carbon atoms. In such a case, the content of the monomer units derived from ethylene and / or an α-olefin having 4 to 12 carbon atoms in the propylene polymer A-1 is preferably 5% by mass or less, more preferably more than 0% by mass to 3% by mass, and even more preferably more than 0% by mass to 1% by mass. Examples of the α-olefin having 4 to 12 carbon atoms include 1-butene, 1-hexene, and 1-octene, and preferably 1-butene.
[0016] The propylene polymer may be a propylene polymer A-2 containing preferably 50% by mass to 90% by mass of monomer units derived from propylene, more preferably 50% by mass to 80% by mass, and further preferably 60% by mass to 80% by mass of monomer units derived from propylene.
[0017] The propylene-based polymer A-2 may be a propylene-ethylene copolymer A-21 containing a monomer unit derived from ethylene. The content of the monomer unit derived from ethylene in the propylene-ethylene copolymer A-21 is preferably 10% by mass to 50% by mass, and from the viewpoint of excellent blocking resistance and bag rupture resistance, is more preferably 20% by mass to 50% by mass, and further preferably 20% by mass to 40% by mass.
[0018] When the film according to the present invention contains a propylene-based polymer A-1 and a propylene-ethylene copolymer A-21 as the olefin polymer, the mass ratio of the propylene-based polymer A-1 to the total mass of the propylene-based polymer A-1 and the propylene-ethylene copolymer A-21 is preferably 50% by mass to 90% by mass, more preferably 60% by mass to 90% by mass, and even more preferably 60% by mass to 80% by mass, from the viewpoint of excellent balance between heat sealability and blocking resistance. The mass ratio of the propylene-ethylene copolymer A-21 to the total mass of the propylene-based polymer A-1 and the propylene-ethylene copolymer A-21 is preferably 10% by mass to 50% by mass, more preferably 10% by mass to 40% by mass, and even more preferably 20% by mass to 40% by mass, from the viewpoint of excellent balance between heat sealability and blocking resistance.
[0019] The film according to the present embodiment may contain a propylene-based polymer composition containing at least two kinds of propylene-based polymers as described above. The combination of at least two kinds of propylene-based polymers contained in the propylene-based polymer composition may be, for example, a combination of propylene homopolymers (e.g., propylene homopolymers having different physical properties, molecular weight, molecular weight distribution, and / or stereoregularity), a combination of a propylene homopolymer and a propylene-based copolymer, or a combination of propylene-based copolymers. The at least two kinds of propylene-based polymers contained in the propylene-based polymer composition may be at least two kinds of propylene-based polymers constituting a multistage polymer formed by carrying out a plurality of polymerization steps in stages, or may be at least two kinds of propylene-based polymers polymerized separately. Preferably, the propylene-based polymer composition contains a propylene-based multistage polymer composed of at least two kinds of propylene-based polymers.
[0020] The propylene-based polymer composition may, for example, have a cold xylene soluble content of 5% by mass to 25% by mass, and the intrinsic viscosity [η] of the cold xylene soluble portion. CXS is 1.5 dL / g to 3.5 dL / g, the content of the cold xylene insolubles is 75% by mass to 95% by mass, and the intrinsic viscosity [η] of the cold xylene insolubles is CXIS The propylene-based polymer composition (A) preferably has a cold xylene soluble portion content of 5% by mass to 20% by mass, more preferably 10% by mass to 20% by mass. The propylene-based polymer composition (A) has an intrinsic viscosity [η] of the cold xylene soluble portion. CXS is preferably 1.7 dL / g to 3.2 dL / g, more preferably 2.0 dL / g to 3.2 dL / g. The propylene-based polymer composition (A) has a cold xylene insoluble content of preferably 80 mass% to 95 mass%, more preferably 80 mass% to 90 mass%. The propylene-based polymer composition (A) has a cold xylene insoluble content of preferably 80 mass% to 95 mass%, more preferably 80 mass% to 90 mass%. CXISis preferably 1.5 dL / g to 2.5 dL / g, and more preferably 1.5 dL / g to 2.0 dL / g. The content of the propylene polymer composition (A) in the film according to this embodiment is preferably 75 mass % to 95 mass %, more preferably 80 mass % to 95 mass %, and even more preferably 80 mass % to 90 mass %.
[0021] The content of cold xylene solubles and the intrinsic viscosity [η] of the cold xylene solubles CXS , the content of cold xylene insolubles, and the intrinsic viscosity [η] of cold xylene insolubles CXIS The value can be changed by changing the type, content, composition distribution, and molecular weight of the monomer derived from ethylene and / or α-olefins having 4 to 12 carbon atoms. In addition, the content of the cold xylene soluble part, the intrinsic viscosity [η] of the cold xylene soluble part CXS , the content of cold xylene insolubles, and the intrinsic viscosity [η] of cold xylene insolubles CXIS can be determined by the method described in the Examples below.
[0022] The propylene polymer composition contained in the film according to the present embodiment may, for example, satisfy the following formula (3) (hereinafter, also referred to as "propylene polymer composition (C)"). The content of the propylene polymer composition (C) in the film is preferably 5% by mass to 30% by mass, more preferably 5% by mass to 25% by mass, and further preferably 5% by mass to 20% by mass. MT C >70×MFR C-1.1 (3) (In the formula, MT C indicates the melt tension (mN) measured at a temperature of 190° C. and a take-up speed of 15.7 m / min. MFR C indicates the melt flow rate (g / 10 min) measured at a temperature of 230°C and a load of 2.16 kg.
[0023] The melt tension can be changed by changing the molecular weight, the branching degree of the molecular chain, or the crosslinking degree between the molecular chains of the propylene polymer contained in the propylene polymer composition. C The melt tension and MFR can be changed by changing the molecular weight of the propylene polymer contained in the propylene polymer composition. C can be determined by the method described in the Examples below.
[0024] The method for producing the propylene-based polymer is not particularly limited. For example, the method for producing the propylene-based polymer A-1 and the propylene-ethylene copolymer A-21 includes a method for polymerizing the raw material propylene or ethylene using a Ziegler-Natta catalyst or a metallocene catalyst. The polymerization method for the propylene-based polymer A-1 and the propylene-ethylene copolymer A-21 includes a method for polymerizing in an inert solvent such as hexane, heptane, toluene, or xylene, a method for polymerizing in liquid propylene or ethylene, a method for adding a catalyst to gaseous propylene or ethylene and polymerizing in a gas phase state, or a method for polymerizing in a combination of these.
[0025] In addition, from the viewpoint of productivity, the method for producing the propylene polymer A-1 and the propylene-ethylene copolymer A-21 is preferably a method in which a first step is carried out to produce the propylene polymer A-1 substantially in the absence of an inert solvent, and then a second step is carried out to produce the propylene-ethylene copolymer A-21 by polymerizing propylene and ethylene in a gas phase in the presence of the propylene polymer A-1. This makes it possible to produce a propylene multistage polymer including the propylene polymer A-1 and the propylene-ethylene copolymer A-21. The method for adjusting the content of the monomer unit derived from ethylene in such a propylene-based multistage polymer includes a method of adding a molecular weight regulator such as hydrogen gas or a metal compound and ethylene in appropriate amounts in each step of polymerization, and a method of adjusting the temperature and pressure during polymerization. The production ratio of the propylene-based polymer A-1 and the propylene-ethylene copolymer A-21 can be controlled by the polymerization time in the first step and the second step, the size of the polymerization tank, the amount of the polymer held in the polymerization tank, the polymerization temperature, the polymerization pressure, and the like. If necessary, drying may be performed at a temperature below the melting temperature of polypropylene in order to remove the residual solvent of polypropylene and ultra-low molecular weight oligomers by-produced during production. Examples of the drying method include the methods described in JP-A-55-75410 and JP Patent No. 2565753.
[0026] The melt flow rate of the above propylene-based polymer composition (A) measured at 230°C under a load of 2.16 kg is preferably 0.001 g / 10 min to 10 g / 10 min, more preferably 0.01 g / 10 min to 10 g / 10 min, and even more preferably 0.01 g / 10 min to 5 g / 10 min, from the viewpoint of improving the processability and hygienic properties of the film.
[0027] The melt flow rate can be varied by changing the molecular weight of the propylene polymer, and can be determined by the method described in the following examples.
[0028] The film according to this embodiment may contain an ethylene-based polymer (B) as the at least two kinds of olefin-based polymers, in addition to the propylene-based polymer. The ethylene-based polymer (B) is a polymer containing more than 50% by mass of monomer units derived from ethylene, and may be an ethylene homopolymer or an ethylene copolymer.
[0029] In such a case, the content of the propylene polymer composition (A) is preferably 70% by mass to 98% by mass, more preferably 75% by mass to 95% by mass, and even more preferably 80% by mass to 95% by mass, based on 100% by mass of the total of the propylene polymer composition (A) and the ethylene polymer (B). Also, the content of the ethylene polymer (B) is preferably 2% by mass to 30% by mass, more preferably 5% by mass to 30% by mass, and even more preferably 5% by mass to 25% by mass, based on 100% by mass of the total of the propylene polymer composition (A) and the ethylene polymer (B).
[0030] Examples of the ethylene-based polymer (B) include ethylene-α-olefin copolymers. The ethylene-α-olefin copolymers contain monomer units derived from ethylene and monomer units derived from an α-olefin having 4 to 12 carbon atoms (preferably 4 to 8 carbon atoms). The content of the monomer units derived from ethylene in the ethylene-α-olefin copolymer is preferably 70% by mass to 95% by mass, more preferably 75% by mass to 95% by mass, and even more preferably 80% by mass to 95% by mass. The content of the monomer units derived from an α-olefin having 4 to 12 carbon atoms (preferably 4 to 8 carbon atoms) in the ethylene-α-olefin copolymer is preferably 5% by mass to 30% by mass, more preferably 5% by mass to 25% by mass, and even more preferably 5% by mass to 20% by mass. Examples of the α-olefin having 4 to 12 carbon atoms include 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 4-methyl-1-pentene, and 4-methyl-1-hexene. The monomer unit derived from the α-olefin having 4 to 12 carbon atoms may be a monomer unit derived from one kind of α-olefin alone, or may be a monomer unit derived from two or more kinds of α-olefins. From the viewpoint of improving the heat seal strength, the α-olefin having 4 to 12 carbon atoms is preferably 1-hexene.
[0031] The density of the ethylene-α-olefin copolymer is preferably 850 kg / m 3 ~950kg / m3 and more preferably 850 kg / m 3 ~930kg / m 3 and more preferably 880 kg / m 3 ~930kg / m 3 The density of ethylene-α-olefin copolymer is 850 kg / m 3 By setting the value to 950 kg / m or more, a film excellent in terms of rigidity can be obtained. 3 By satisfying the following conditions, a film having excellent resistance to bag rupture can be obtained.
[0032] The melt flow rate of the ethylene-α-olefin copolymer measured at 190° C. under a load of 2.16 kg is preferably 0.1 g / 10 min to 50 g / 10 min, more preferably 0.1 g / 10 min to 10 g / 10 min, and even more preferably 1 g / 10 min to 5 g / 10 min.
[0033] The melt flow rate can be varied by changing the molecular weight of the ethylene-α-olefin copolymer, and can be determined by the method described in the following examples.
[0034] The molecular weight distribution of the ethylene-α-olefin copolymer is preferably 1 or more and 5 or less, more preferably 1 or more and 4 or less, and even more preferably 2 or more and 4 or less. When the molecular weight distribution of the ethylene-α-olefin copolymer is 1 or more, the extrusion load is reduced and the processability is good. When the molecular weight distribution of the ethylene-α-olefin copolymer is 5 or less, a film with excellent resistance to rupture can be obtained. Here, the "molecular weight distribution" refers to the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) measured under the following conditions using gel permeation chromatography (hereinafter sometimes referred to as "GPC"). The baseline on the chromatogram was a straight line connecting the points of a stable horizontal region where the retention time is sufficiently shorter than the appearance of the sample elution peak and the points of a stable horizontal region where the retention time is sufficiently longer than the observation of the solvent elution peak. Apparatus: Waters 150C Separation column: TOSOH TSK-GEL GMH6-HT Measurement temperature: 140℃ Carrier: Orthodichlorobenzene Flow rate: 1.0mL / min Injection volume: 500μL Detector: Differential Refraction Molecular weight standard: Standard polystyrene
[0035] As a method for adjusting the molecular weight distribution of the ethylene-α-olefin copolymer to the above range, for example, a method is used in which ethylene and an α-olefin are copolymerized using a metallocene catalyst to adjust the density of the ethylene-α-olefin copolymer to 850 kg / m 3 ~950kg / m 3 The following method is exemplified.
[0036] The ethylene-α-olefin copolymer can be produced, for example, by using a metallocene catalyst. The metallocene catalyst is, for example, an olefin polymerization catalyst using a transition metal compound having a group with a cyclopentadiene-type anion skeleton (hereinafter also referred to as a "metallocene-based transition metal compound").
[0037] An example of the metallocene transition metal compound is a compound represented by the following formula (X). MLaXn-a···(X) (In the formula, M is a transition metal atom of Group 4 or the lanthanide series of the Periodic Table of the Elements. L is a group having a cyclopentadiene anion skeleton or a group containing a hetero atom, and at least one of L is a group having a cyclopentadiene anion skeleton. A plurality of L's may be crosslinked to each other. X is a halogen atom, a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms. n represents the valence of the transition metal atom. a is an integer satisfying 0 < a ≤ n)
[0038] Examples of the metallocene transition metal compound represented by the above formula include bis(1,3-n-butylmethylcyclopentadienyl)zirconium dichloride, bis(1,3-n-propylmethylcyclopentadienyl)zirconium dichloride, bis(n-butylcyclopentadienyl)zirconium dichloride, bis(1,3-dimethylcyclopentadienyl)zirconium dichloride, bis(1,3-diethylcyclopentadienyl)zirconium dichloride, ethylenebis(indenyl)zirconium dichloride, ethylenebis(4-methyl-1-indenyl)zirconium dichloride, ethylenebis(4,5,6,7-tetrahydro-1-indenyl)zirconium dichloride, and the like.
[0039] The above metallocene transition metal compound is preferably used in contact with an activating cocatalyst. Examples of the activating cocatalyst include an aluminoxane compound, and an activating cocatalyst obtained by using an organoaluminum compound in combination with a boron compound such as trityl borate or anilinium borate. Further, it may be used in combination with a particulate carrier containing an inorganic carrier such as SiO2 or Al2O3, or an organic carrier such as a polymer such as ethylene or styrene.
[0040] When the film according to this embodiment contains the above propylene-based polymer A-1 and the above propylene-ethylene copolymer A-21, the propylene-based polymer A-1 is preferably contained in an amount of 60% by mass to 95% by mass, more preferably 65% by mass to 95% by mass, and still more preferably 65% by mass to 90% by mass, based on the total mass of all the polymers in the film, and the above propylene-ethylene copolymer A-21 is preferably contained in an amount of 5% by mass to 40% by mass, more preferably 5% by mass to 35% by mass, and still more preferably 10% by mass to 35% by mass.
[0041] When the film according to this embodiment contains the propylene polymer A-1 and the propylene-ethylene copolymer A-21, and an ethylene-α-olefin copolymer as the ethylene polymer (B), the film contains, relative to the total mass of all polymers in the film, preferably 40% by mass to 90% by mass, more preferably 40% by mass to 85% by mass, and even more preferably 45% by mass to 85% by mass of the propylene polymer A-1, preferably 5% by mass to 40% by mass, more preferably 5% by mass to 35% by mass, and even more preferably 10% by mass to 35% by mass of the ethylene-α-olefin copolymer, preferably 5% by mass to 30% by mass, more preferably 5% by mass to 25% by mass, and even more preferably 5% by mass to 20% by mass of the ethylene-α-olefin copolymer.
[0042] In addition, when the film according to the present embodiment includes the propylene-based polymer A-1 and the propylene-ethylene copolymer A-21, and the ethylene-α-olefin copolymer as the ethylene-based polymer (B), the ratio of the total mass of the propylene-based polymer A-1 and the propylene-ethylene copolymer A-21 to the total mass of the propylene-based polymer A-1, the propylene-ethylene copolymer A-21, and the ethylene-α-olefin copolymer is preferably 70% by mass to 95% by mass, more preferably 75% by mass to 95% by mass, and even more preferably 75% by mass to 93% by mass. When the ratio of the total mass of the propylene-based polymer A-1 and the propylene-ethylene copolymer A-21 is within the above range, a film having good heat sealability can be obtained.
[0043] The film according to the present embodiment may further contain a phosphate metal salt nucleating agent. The content of the phosphate metal salt nucleating agent in the film is preferably 100 to 10,000 ppm, more preferably 100 ppm to 5,000 ppm, and further preferably 500 ppm to 5,000 ppm.
[0044] Examples of the phosphate metal salt-based nucleating agent include aromatic phosphate metal salts, etc. Specifically, sodium bis(4-t-butylphenyl) phosphate, sodium bis(4-methylphenyl) phosphate, sodium bis(4-ethylphenyl) phosphate, sodium bis(4-i-propylphenyl) phosphate, sodium bis(4-t-octylphenyl) phosphate, potassium bis(4-t-butylphenyl) phosphate, calcium bis(4-t-butylphenyl) phosphate, and magnesium bis(4-t-butylphenyl) phosphate. , lithium bis(4-t-butylphenyl) phosphate, aluminum bis(4-t-butylphenyl) phosphate, sodium 2,2'-methylene bis(4,6-di-t-butylphenyl) phosphate, sodium 2,2'-ethylidene bis(4,6-di-t-butylphenyl) phosphate, lithium 2,2'-methylene bis(4,6-di-t-butylphenyl) phosphate, lithium 2,2'-ethylidene bis(4,6-di-t-butylphenyl) phosphate, sodium Lithium 2,2'-ethylidene bis(4-i-propyl-6-t-butylphenyl) phosphate, Lithium 2,2'-methylene bis(4-methyl-6-t-butylphenyl) phosphate, Lithium 2,2'-methylene bis(4-ethyl-6-t-butylphenyl) phosphate, Calcium bis[2,2'-thiobis(4-methyl-6-t-butylphenyl) phosphate], Calcium bis[2,2'-thiobis(4-ethyl-6-t-butylphenyl) phosphate], Calcium bis[2 ,2'-thiobis-(4,6-di-t-butylphenyl)phosphate], magnesium bis[2,2'-thiobis(4,6-di-t-butylphenyl)phosphate], magnesium bis[2,2'-thiobis-(4-t-octylphenyl)phosphate], sodium 2,2'-butylidene-bis(4,6-di-methylphenyl)phosphate, sodium 2,2'-butylidene-bis(4,6-di-t-butylphenyl)phosphate, sodium 2,2'-t-octylmethylene-bis(4,6-di-methylphenyl) phosphate, sodium 2,2'-t-octylmethylene-bis(4,6-di-t-butylphenyl) phosphate, calcium bis[2,2'-methylene-bis(4,6-di-t-butylphenyl) phosphate], magnesium bis[2,2'-methylene-bis(4,6-di-t-butylphenyl) phosphate], barium bis[2,2'-methylene-bis(4,6-di-t-butylphenyl) phosphate], sodium Thorium-2,2'-methylene-bis(4-methyl-6-t-butylphenyl)phosphate, sodium-2,2'-methylene-bis(4-ethyl-6-t-butylphenyl)phosphate, sodium-(4,4'-dimethyl-5,6'-di-t-butyl-2,2'-biphenyl)phosphate, calcium-bis[(4,4-dimethyl-6,6'-di-t-butyl-2,2'-biphenyl)phosphate], sodium-2,2'-ethylidene-bis( 4-m-butyl-6-t-butylphenyl) phosphate, sodium 2,2'-methylene-bis(4,6-dimethylphenyl) phosphate, sodium 2,2'-methylene-bis(4,6-diethylphenyl) phosphate, potassium 2,2'-ethylidene-bis(4,6-di-t-butylphenyl) phosphate, calcium bis[2,2'-ethylidene-bis(4,6-di-t-butylphenyl) phosphate], magnesium bis[ Examples of suitable phosphates include 2,2'-ethylidene-bis(4,6-di-t-butylphenyl)phosphate, barium-bis[2,2'-ethylidene-bis(4,6-di-t-butylphenyl)phosphate], aluminum-tris[2,2'-methylene-bis(4,6-di-t-butylphenyl)phosphate] and aluminum-tris[2,2'-ethylidene-bis(4,6-di-t-butylphenyl)phosphate] and mixtures of two or more of these. Sodium-2,2'-methylene-bis(4,6-di-t-butylphenyl)phosphate is particularly preferred.
[0045] The film according to the present embodiment may contain additives or other resins as necessary. Examples of additives include antioxidants, neutralizing agents, ultraviolet absorbers, antistatic agents, lubricants, nucleating agents, adhesives, antifogging agents, antiblocking agents, and melt flow rate regulators. Examples of antioxidants include phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants, and a composite antioxidant having a unit having both a phenol-based antioxidant mechanism and a phosphorus-based antioxidant mechanism in one molecule can also be used. Other resins include elastomers such as styrene-based copolymer rubber obtained by hydrogenating styrene-butadiene-styrene copolymers and styrene-isoprene-styrene copolymers.
[0046] The method for producing a film configured as described above includes a melt-kneading step of melt-kneading a mixture containing at least two kinds of propylene-based polymers, an ethylene-based polymer, and a phosphate metal salt-based nucleating agent. The method for producing a film also includes an extrusion step of extruding the kneaded product obtained in the melt-kneading step into a sheet, and a cooling step of pressing the sheet-like kneaded product obtained in the extrusion step against a cooling roll with gas blown out of an air chamber to cool it. The method for producing a film also includes a film-forming step of forming a film by forming the sheet-like kneaded product into a film.
[0047] In the melt-kneading step, for example, the propylene-based polymer composition (A) and the ethylene-based polymer (B), preferably the propylene-based polymer composition (C), may be melt-kneaded. The melt-kneading step is preferably carried out by adding the various additives.
[0048] The melt-kneading step can be carried out using a conventionally known method and device. For example, the above-mentioned materials (e.g., pellet-shaped materials) are mixed using a mixing device such as a Henschel mixer, a ribbon blender, or a tumble mixer, and then melt-kneaded. Alternatively, the above-mentioned materials are continuously fed at a constant ratio using a constant-rate feeder to obtain a homogeneous mixture, and then the mixture is melt-kneaded using a single-screw or twin-screw or more extruder, a Banbury mixer, a roll kneader, or the like. The melt-kneading temperature is preferably 190°C to 320°C, more preferably 210°C to 280°C.
[0049] The extrusion step can be carried out using a method and apparatus known in the art, such as a T-die method or a tubular method, with the T-die method being preferred.
[0050] The air chamber used in the cooling step is installed close to the cooling roll. The air chamber is a box-structured device with an opening at a portion facing the cooling roll. A conventionally known device can be used as the air chamber. The air chamber is configured to receive gas from a blower connected by a duct to increase the air pressure in the internal space, and to blow the gas from the opening with an air volume and air pressure corresponding to the air pressure. As a result, the sheet-like kneaded material extruded from the T-die is pressed against the cooling roll by the gas blown from the air chamber to make it adhere to the cooling roll. Examples of the gas introduced into the air chamber include air, nitrogen, and carbon dioxide gas. The temperature of the gas can be, for example, preferably 10°C to 50°C.
[0051] The cooling step is performed by adjusting the amount of gas blown out of the air chamber so that the gas pressure in the air chamber is 50 Pa to 300 Pa, preferably 50 Pa to 250 Pa, and more preferably 100 Pa to 250 Pa. In the cooling step, a sheet-like kneaded material is supplied between the air chamber and the cooling roll. Then, gas is blown from the air chamber onto the sheet-like kneaded material to bring the sheet-like kneaded material into close contact with the cooling roll.
[0052] The air chamber has an opening (gas outlet) for blowing gas in the horizontal direction, and the gas outlet is disposed at a position on the side of the cooling roll, spaced apart from the cooling roll. The shortest distance between the gas outlet and the cooling roll is preferably 0.01 cm to 5 cm, more preferably 0.01 cm to 1 cm, in the horizontal direction. The width of the opening (gas outlet) of the air chamber is preferably configured to be wider than the width of the sheet-like kneaded material (i.e., the width of the blown airflow is wider than the sheet-like kneaded material). This allows the sheet-like kneaded material to be pressed uniformly against the cooling roll.
[0053] The surface temperature of the cooling roll is preferably 20°C to 80°C, and more preferably 20°C to 70°C.
[0054] The film-forming step may be performed by contacting the sheet-like kneaded material obtained in the extrusion step with a cooling roll (i.e., may be performed simultaneously with the cooling step), or may be performed after the cooling step. When the film-forming step is performed after the cooling step, for example, the sheet-like kneaded material after the cooling step may be sandwiched between nip rolls to form a film of a predetermined thickness.
[0055] The film according to the present embodiment can be used as a sealant layer of a multi-layer film. The film forming the other layer laminated on the sealant layer is not particularly limited. For example, a barrier film such as a stretched nylon film, an aluminum foil, or a polyvinylidene chloride film, or a transferable film such as a nylon film, a biaxially stretched polypropylene film, or a polyethylene terephthalate film can be mentioned. For example, a method for bonding the films together can be a dry lamination method or an extrusion lamination method.
[0056] The thickness of the film according to this embodiment is preferably 5 to 500 μm, and more preferably 30 to 150 μm.
[0057] A multilayer film including the film according to the present embodiment as a sealant can be used in packaging applications for packaging items such as food, textiles, miscellaneous goods, etc. For example, the multilayer film can be used as a material for forming a packaging bag, preferably a material for a packaging bag for retort food.
[0058] The film according to the present embodiment may be subjected to a surface treatment such as a corona discharge treatment, a flame treatment, a plasma treatment, or an ozone treatment by a method generally used industrially.
[0059] As described above, according to the present embodiment, it is possible to provide a film that has resistance to bag rupture and is relatively easy to cut, and to provide a method for producing such a film.
[0060] In other words, the film according to this embodiment has an islands-in-a-sea type phase-separated structure consisting of a continuous phase and a discontinuous phase due to at least two types of olefin-based polymers, and the degree of orientation in the MD direction of the film determined by wide-angle X-ray scattering measurement is within the above-mentioned range, so that the film has resistance to bag rupture and is relatively easy to cut.
[0061] Furthermore, by satisfying the above formulas (1) and (2), the film according to this embodiment has excellent resistance to bag breakage and can be easily cut.
[0062] Furthermore, since the film according to the present embodiment contains the propylene polymer composition (A), a film having excellent resistance to bag rupture can be obtained.
[0063] Furthermore, the film according to the present embodiment contains the propylene-based polymer composition (A) and the ethylene-based polymer (B) in the above-mentioned ratio, so that a film having excellent resistance to bag rupture can be obtained.
[0064] Furthermore, by containing the phosphate metal salt-based nucleating agent in the above-mentioned ratio, the film according to this embodiment can have excellent resistance to bag breakage and excellent ease of cutting.
[0065] In addition, by containing the propylene-based polymer composition (C) satisfying the above formula (3) in the above ratio, the film according to the present embodiment can have excellent resistance to bag rupture and ease of cutting.
[0066] Furthermore, in the film manufacturing method according to this embodiment, by setting the gas pressure in the air chamber in the cooling step within the above range, it is possible to produce a film that has bag-breaking resistance and is relatively easy to cut.
[0067] The film and the method for producing the film according to the present invention are not limited to the above-mentioned embodiment, and various modifications are possible without departing from the gist of the present invention. In addition, the configurations and methods of the above and following embodiments may be arbitrarily adopted and combined (the configurations and methods of one embodiment may be applied to the configurations and methods of other embodiments). EXAMPLES
[0068] The measured values of each item in the examples and comparative examples were measured by the following methods.
[0069] The contents of the propylene polymer and the propylene-ethylene copolymer contained in the propylene polymer composition are obtained from the mass balance during the polymerization of each of them.
[0070] The content of the monomer units derived from ethylene contained in the propylene-ethylene copolymer contained in the propylene polymer composition was calculated by measuring the IR spectrum of the entire propylene polymer composition and calculating it according to the following formula (4) in accordance with "(ii) Method for block copolymers" described on page 616 of Polymer Analysis Handbook (published by Kinokuniya Shoten in 1995). Here, ET, EA, and EB in the following formula (4) respectively represent the content of the monomer units derived from ethylene in the entire propylene polymer composition, the content of the monomer units derived from ethylene in the propylene polymer, and the content of the monomer units derived from ethylene in the propylene-ethylene copolymer, and PA and PB respectively represent the content of the propylene polymer and the propylene-ethylene copolymer. EB = (ET - EA × PA) / PB (4)
[0071] (1) Melt flow rate (MFR, unit: g / 10 min) The melt flow rate of the propylene-based polymer composition was measured at a temperature of 230° C. under a load of 2.16 kg in accordance with the method specified in JIS K7210. The melt flow rate of the ethylene polymer was measured at a temperature of 190° C. under a load of 2.16 kg in accordance with the method specified in JIS K7210.
[0072] (2) Cold xylene solubles (CXS, unit: mass%) 0.5 g of the propylene-based polymer composition was dissolved in 100 mL of boiling xylene, and the resulting solution was cooled to 0°C and left at the same temperature for 0.5 hours. The xylene solution was then heated to 20°C and stirred at the same temperature for 1 hour. The resulting mixture was filtered to separate the precipitate and the solution, and the propylene-based polymer in the solution was quantified by liquid chromatography to measure the amount of cold xylene solubles. The measurement conditions for the liquid chromatography were as follows. Column: SHODEX GPC KF-801 Eluent: Tetrahydrofuran Sample injection volume: 100 μL Flow rate: 1.5mL / min Detector: Differential refractometer
[0073] (3) Intrinsic viscosity ([η], unit: dL / g) The intrinsic viscosity of the propylene polymer composition was measured in tetralin (1,2,3,4-tetrahydronaphthalene) at 135° C. using an Ubbelohde viscometer. Intrinsic viscosity [η] of the cold xylene insoluble part of the propylene polymer composition CXIS is the intrinsic viscosity [η] of the propylene-based polymer composition and the intrinsic viscosity [η] of the cold xylene-soluble portion of the propylene-based polymer composition CXS and weight, using the following formula (5). [η] CXIS =([η]×100-[η] CXS ×W CXS ) / W CXIS (5) (In the formula, [η] CXIS indicates the intrinsic viscosity (dL / g) of the cold xylene insoluble portion of the propylene-based polymer composition. [η] represents the intrinsic viscosity (dL / g) of the propylene polymer composition. [η] CXS indicates the intrinsic viscosity (dL / g) of the cold xylene soluble portion of the propylene-based polymer composition. W CXS indicates the content (mass%) of the cold xylene soluble portion in the propylene-based polymer composition. W CXIS indicates the content (mass%) of the cold xylene insoluble matter in the propylene polymer composition.
[0074] (4) Melt tension (MT, unit: mN) The melt tension of the propylene polymer composition was measured under the following conditions using a melt tension measuring device manufactured by Toyo Seiki Seisakusho.
[0075] Specifically, an orifice with a length of 8.00 mm and an inner diameter of 2.10 mm was attached to a cylinder with an inner diameter of 9.55 mm. The propylene-based polymer composition was then filled into the cylinder, and a piston was inserted and preheated at 190° C. for 5 minutes to fully melt the propylene-based polymer composition. The piston was then lowered at a speed of 5.7 mm / min, and the propylene-based polymer composition melted and extruded from the orifice at 0.32 g / min was taken up at 15.7 m / min, and the tension (mN) acting on the propylene-based polymer composition was measured with a tension detector to be the melt tension.
[0076] (5) Observation of islands-type phase separation structure The sea-island phase separation structure in the monolayer film was observed using a transmission electron microscope. The film was embedded in resin and then stained with an aqueous solution of ruthenium tetroxide. A cross section determined by the MD and ND directions of the film was cut out with a cryomicrotome to prepare an ultrathin sample with a thickness of 200 nm or less. The MD direction is the flow direction of the film during the formation of the monolayer film, and the ND direction is the thickness direction of the film. The ultrathin sample was placed on an observation mesh, and then a cross-sectional image was taken with a transmission electron microscope (Hitachi High-Tech Corporation, H-7650) at an accelerating voltage of 100 kV and an observation magnification of 5000 times.
[0077] (6) Three-dimensional refractive index measurement A test piece with a width of about 50 mm (TD direction) and a length of about 40 mm (MD direction) was cut out from the monolayer film. The TD direction is the width direction of the film when the monolayer film is formed, and the MD direction is the flow direction of the film when the monolayer film is formed. The obtained test piece was subjected to three-dimensional refractive index measurement using a measuring device KOBRA-WR (manufactured by Oji Scientific Instruments Co., Ltd.) and software KOBRA-RE. The test piece was set in the measuring device so that the MD direction and the 0 degree direction in the angle reference of the measuring device KOBRA-WR coincided. The retardation value R(0) (nm) was measured by irradiating light with a wavelength of 589.3 nm from the thickness direction of the film, and the retardation value R(30) (nm) was measured by irradiating light with a wavelength of 589.3 nm from a direction inclined 30° to the thickness direction of the film with the slow axis as the tilt axis. From the obtained R(0) and R(30) and the film thickness d(nm), the refractive index Nx of the slow axis, the refractive index Ny of the fast axis, and the refractive index Nz in the thickness direction of the film were calculated, satisfying the following formulas (6) to (11), with the following formula (12) as a constraint. Here, N' is the refractive index in the incident plane when the incident angle is 30°, β1 is the refraction angle for the refractive index N' when the incident angle is 30°, and β2 is the refraction angle for the refractive index Nx when the incident angle is 30°. In addition, the angle θ(°) between the MD direction of the film and the slow axis was obtained. Nx-Ny=R(0) / d (6) Nx-N'=R(30)×cosβ / d (7) N' = Ny × Nz / (Ny 2 ×sin 2 β1+Nz 2 ×cos 2 β1) 1 / 2 (8) however, β = (β1 + β2) / 2 (9) β1=sin -1 (sin30° / N') (10) β2=sin -1 (sin30° / Nx) (11) (Nx + Ny + Nz) / 3 = 1.4915 (12)
[0078] (7) Wide-angle X-ray scattering measurement A number of test pieces with a width of approximately 2 cm (TD direction) and a length of approximately 2 cm (MD direction) were cut out from the monolayer film. The TD direction is the width direction of the film when the monolayer film is formed, and the MD direction is the flow direction of the film when the monolayer film is formed. Six test pieces were stacked so that the MD directions of the test pieces were aligned, to prepare a test piece for measurement. The obtained test pieces for measurement were subjected to wide-angle X-ray scattering measurement under the following conditions. - Model: Rigaku Nano Viewer ·Tube:Cu-Kα Detector: PILATUS 100k Exposure time: 300 seconds Tube voltage: 40kV Tube current: 20mA Beam diameter: 0.25mmφ With the camera length, which is the distance from the X-ray source to the camera, kept constant, and without setting the test piece for measurement, the transmitted intensity I0 and the scattered intensity I Air The X-ray was set so that it was incident perpendicularly to the surface of the test piece for measurement, and the transmission intensity I t and the scattered diffraction intensity I s I0 and I t The ratio of these is taken as the correction ratio R, and the measured scattering and diffraction intensity I s Then, air scattering correction was performed using the following equations (13) and (14). The corrected scattered diffraction intensity was expressed as I c Let us assume that. R=I t / I0···(13) I c =I s -R×I Air (14) From the X-ray diffraction pattern obtained by the measurement, the diffraction peak of the (040) plane of polypropylene crystal was cwas plotted every 0.2° in the circumferential direction to create an azimuth angle profile. Using the peaks that appeared on the TD side of the test specimen, the peak height was determined as the distance from the bottom to the top of the peak, and the half-width W, which is the peak width at which the peak height is half, was calculated. The sum of the half-widths of the peaks that appeared on the TD side was taken as ΣW, and the degree of orientation F (%) in the MD was calculated using the following formula (15). F=(360-ΣW)×100 / 360···(15)
[0079] (8) Tear strength evaluation Based on JIS K7128-2 (Elmendorf tear method), the tear strength of the monolayer film was measured under the following conditions. A test piece with a width of 76 mm (TD direction) and a length of 63 mm (MD direction) was cut out from the monolayer film. The TD direction is the width direction of the film when the monolayer film is formed, and the MD direction is the flow direction of the film when the monolayer film is formed. The obtained test piece was placed in a thermostatic chamber at 23°C, and then a 20 mm cut was made in the length direction from the end of the center of the width. Next, the test piece was attached to the grip of a digital Elmendorf tear tester (manufactured by Toyo Seiki Co., Ltd.) and the tear strength was measured. The value (N) obtained by tearing was divided by the thickness (mm) of the test piece and used as the tear strength (N / mm).
[0080] (9) Drop bag strength evaluation A composite film was used in which a monolayer film, an aluminum foil having a thickness of 7 μm, and a polyethylene terephthalate film having a thickness of 12 μm were laminated in the order described above by a dry lamination method. Then, the monolayer film surface was folded inward using a standing pouch bag making machine manufactured by Seibu Machinery Co., Ltd., and the three sides were heat-sealed three times at 240°C for 0.5 seconds to produce a packaging bag. After filling the obtained packaging bag with 160 g of water, the remaining side that was not heat-sealed was heat-sealed for 1.0 seconds using an impulse sealer to produce a water-filled packaging bag having a length of 150 mm and a width of 130 mm. After conditioning the water-filled packaging bag for 24 hours at 5°C, a test was performed by dropping it repeatedly 20 times from a height of 16 cm. The test was performed on 12 bags each, and the drop strength was evaluated based on the total number of times that the bag did not break. If the bag did not break at all, it was scored as 240 points, and if all the bags broke in one try, it was scored as 0 points.
[0081] The components used in the examples and comparative examples are as follows.
[0082] [Propylene-based polymer composition (a-1)] In the first step, propylene was polymerized in a gas phase using a Ziegler-Natta catalyst, and then in the second step, propylene and ethylene were copolymerized in a gas phase to obtain a propylene-based multistage polymer consisting of a propylene homopolymer (a-11) and a propylene-ethylene copolymer (a-12). The obtained propylene-based multistage polymer had a propylene homopolymer (a-11) content of 70% by mass, a propylene-ethylene copolymer (a-12) content of 30% by mass, and a monomer unit content derived from ethylene in the propylene-ethylene copolymer (a-12) of 30% by mass. 0.005 parts by mass of calcium hydroxide, 0.075 parts by mass of Sumilizer GP (manufactured by Sumitomo Chemical Co., Ltd.), and 0.03 parts by mass of Sumilizer GS (manufactured by Sumitomo Chemical Co., Ltd.) were mixed with 100 parts by mass of the obtained propylene-based multistage polymer, and then melt-kneaded to obtain a propylene-based polymer composition (a-1). The propylene polymer composition (A-1) had a cold xylene insoluble content of 81% by mass, and its intrinsic viscosity ([η] CXIS) is 1.82 dl / g, the cold xylene solubles content is 19 mass%, and its intrinsic viscosity ([η] CXS ) was 2.95 dl / g, and the melt flow rate was 3.1 g / 10 min.
[0083] [Propylene-based polymer composition (a-2)] In the first step, propylene was polymerized in a gas phase using a Ziegler-Natta catalyst, and then in the second step, propylene and ethylene were copolymerized in a gas phase to obtain a propylene-based multistage polymer consisting of a propylene homopolymer (a-21) and a propylene-ethylene copolymer (a-22). The obtained propylene-based multistage polymer had a propylene homopolymer (a-21) content of 84% by mass, a propylene-ethylene copolymer (a-22) content of 16% by mass, and a monomer unit content derived from ethylene in the propylene-ethylene copolymer (a-22) of 40% by mass. 0.005 parts by mass of calcium hydroxide, 0.075 parts by mass of Sumilizer GP (manufactured by Sumitomo Chemical Co., Ltd.), and 0.03 parts by mass of Sumilizer GS (manufactured by Sumitomo Chemical Co., Ltd.) were mixed with 100 parts by mass of the obtained propylene multistage polymer, and then melt-kneaded to obtain a propylene-based polymer composition (a-2). The propylene polymer composition (a-2) has a cold xylene insoluble content of 90 mass %, and its intrinsic viscosity ([η] CXIS ) is 1.56 dl / g, the cold xylene soluble content is 10 mass%, and its intrinsic viscosity ([η] CXS ) was 2.00 dl / g, and the melt flow rate was 7.0 g / 10 min.
[0084] [Propylene-based polymer composition (a-3)] In the first step, propylene was polymerized in a gas phase using a Ziegler-Natta catalyst, and then in the second step, propylene and ethylene were copolymerized in a gas phase to obtain a propylene-based multistage polymer consisting of a propylene homopolymer (a-31) and a propylene-ethylene copolymer (a-32). The obtained propylene-based multistage polymer had a propylene homopolymer (a-31) content of 77% by mass, a propylene-ethylene copolymer (a-32) content of 23% by mass, and a monomer unit content derived from ethylene in the propylene-ethylene copolymer (a-32) of 30% by mass. 0.005 parts by mass of calcium hydroxide, 0.075 parts by mass of Sumilizer GP (manufactured by Sumitomo Chemical Co., Ltd.), and 0.075 parts by mass of Sumilizer GS (manufactured by Sumitomo Chemical Co., Ltd.) were mixed with 100 parts by mass of the obtained propylene-based multistage polymer, and then melt-kneaded to obtain a propylene-based polymer composition (a-3). The propylene polymer composition (a-3) had a cold xylene insoluble content of 84 mass%, and its intrinsic viscosity ([η] CXIS ) is 1.93 dl / g, the cold xylene solubles content is 16 mass%, and its intrinsic viscosity ([η] CXS ) was 3.03 dl / g, and the melt flow rate was 2.5 g / 10 min.
[0085] [Ethylene-based polymer (b-1)] An ethylene-butene copolymer (manufactured by Sumitomo Chemical Co., Ltd., product name: Sumikathene L GA401) was used. The melt flow rate was 3.0 g / 10 min and the density was 935 kg / m 3 It was.
[0086] [Ethylene-based polymer (b-2)] An ethylene-butene copolymer (manufactured by Mitsui Chemicals, Inc., product name: TAFMER A4085s) was used. The melt flow rate was 3.6 g / 10 min and the density was 885 kg / m 3 It was.
[0087] [Propylene-based polymer composition (c-1)] Using a Ziegler-Natta catalyst, a propylene homopolymer (c-11) having an intrinsic viscosity of 7.18 dl / g was produced in the first step, and a propylene homopolymer (c-12) having an intrinsic viscosity of 0.85 dl / g was produced in the second step to obtain a propylene-based multistage polymer. The obtained propylene-based multistage polymer had a content of 19% by mass of the propylene homopolymer (c-11) produced in the first step and a content of 81% by mass of the propylene homopolymer (c-12) produced in the second step. 0.050 parts by mass of calcium stearate, 0.2 parts by mass of Irganox 1010 (manufactured by BASF), and 0.025 parts by mass of Irgafos 168 (manufactured by BASF) were mixed with 100 parts by weight of this propylene-based multistage polymer, and then melt-kneaded to obtain a propylene-based polymer composition (c-1). The propylene polymer composition (c-1) had a melt flow rate of 8.9 g / 10 min and a melt tension of 25.7 mN.
[0088] [Composition (d) containing one propylene polymer] Propylene was polymerized using a Ziegler-Natta catalyst to obtain a propylene homopolymer. 100 parts by weight of the obtained propylene homopolymer were mixed with 0.002 parts by weight of calcium hydroxide and 0.15 parts by weight of Irganox 1010 (BASF), and then melt-kneaded to obtain a composition (d) containing one type of propylene-based polymer. The melt flow rate of the obtained composition (d) was 8.0 g / 10 min.
[0089] [Phosphate metal salt nucleating agent masterbatch (MB)] Propylene was polymerized using a Ziegler-Natta catalyst to obtain a propylene homopolymer. 94% by mass of the obtained propylene homopolymer was mixed with 6% by mass of phosphate metal salt, Adeka STAB NA-11 (sodium-2,2'-methylene-bis(4,6-di-tert-butylphenyl)phosphate, manufactured by ADEKA Corporation). 0.01 parts by mass of hydrotalcite, 0.1 parts by mass of Irganox 1010 (manufactured by BASF), and 0.05 parts by mass of Sumilizer GP (manufactured by Sumitomo Chemical Co., Ltd.) were mixed with 100 parts by mass of the obtained mixture, and then melt-kneaded to obtain a phosphate metal salt nucleating agent master batch (MB).
[0090] [Example 1] 42% by mass of a propylene-based polymer composition (a-1), 45% by mass of a propylene-based polymer composition (a-2), 8% by mass of an ethylene-based polymer (b-1), and 5% by mass of a phosphate metal salt nucleating agent master batch (MB) were pellet-blended. The mixture obtained was melt-kneaded with three extruders, and then the resulting molten mixture was combined and introduced into a feed block type T-die (die width 1250 mm, lip opening 0.8 mm) and melt-extruded at a die temperature of 240°C. The extruded molten film was cooled and solidified with a chill roll (cooling roll) rotating at 50 m / min and having a cooling temperature of 50°C, to obtain a monolayer film with a thickness of 70 μm. The obtained monolayer film had a sea-island type phase separation structure. The components contained in the monolayer film are shown in Tables 1 and 2.
[0091] The obtained monolayer film was subjected to three-dimensional refractive index measurement, wide-angle X-ray scattering measurement, and tear strength evaluation. In addition, the composite film produced using the obtained monolayer film was subjected to a bag drop strength evaluation. The evaluation results are shown in Table 3.
[0092] [Example 2] A monolayer film was produced and evaluated in the same manner as in Example 1, except that a mixture obtained by pellet-blending 85% by mass of the propylene-based polymer composition (a-3), 10% by mass of the ethylene-based polymer (b-2), and 5% by mass of the phosphate metal salt nucleating agent master batch (MB) was used. The obtained monolayer film had an island-in-a-sea type phase separation structure. The components contained in the monolayer film are shown in Table 1. The evaluation results are also shown in Tables 2 and 3.
[0093] [Example 3] A monolayer film was produced and evaluated in the same manner as in Example 1, except that a mixture of 75% by mass of the propylene-based polymer composition (a-3), 10% by mass of the propylene-based polymer composition (c), 10% by mass of the ethylene-based polymer (b-2), and 5% by mass of the phosphate metal salt nucleating agent master batch (MB) was used as a pellet blend. The obtained monolayer film had an island-in-a-sea type phase separation structure. The components contained in the monolayer film are shown in Table 1. The evaluation results are also shown in Tables 2 and 3.
[0094] [Comparative Example 1] A monolayer film was produced and evaluated in the same manner as in Example 1, except that the air volume of the air chamber was adjusted so that the air pressure in the air chamber box was 500 Pa. The obtained monolayer film had a sea-island type phase separation structure. The components contained in the monolayer film are shown in Table 1. The evaluation results are also shown in Tables 2 and 3.
[0095] [Comparative Example 2] A monolayer film was produced and evaluated in the same manner as in Example 1, except that 100% by mass of the propylene-based polymer composition (a-3) was used. The obtained monolayer film had a sea-island type phase separation structure. The components contained in the monolayer film are shown in Table 1. The evaluation results are shown in Tables 2 and 3.
[0096] [Comparative Example 3] A monolayer film was produced and evaluated in the same manner as in Example 1, except that a mixture obtained by pellet-blending 90% by mass of the propylene-based polymer composition (a-3) and 10% by mass of the ethylene-based polymer (b-2) was used. The obtained monolayer film had an islands-in-a-sea type phase separation structure. The components contained in the monolayer film are shown in Table 1. The evaluation results are shown in Tables 2 and 3.
[0097] [Comparative Example 4] A monolayer film was produced and evaluated in the same manner as in Example 1, except that a mixture of 95% by weight of a composition (d) containing one type of propylene-based polymer and 5% by weight of a phosphate metal salt nucleating agent master batch (MB) was used as a pellet blend. The obtained monolayer film did not have an islands-in-a-sea type phase separation structure. The components contained in the monolayer film are shown in Table 1. The evaluation results are also shown in Tables 2 and 3.
[0098] [Table 1]
[0099] [Table 2]
[0100] [Table 3]
Claims
1. A film containing at least two kinds of olefin polymers, the at least two kinds of olefin polymers form an islands-in-a-sea type phase-separated structure consisting of a continuous phase and a discontinuous phase, The degree of orientation in the MD direction of the film determined by wide-angle X-ray scattering measurement is 76% or more, the at least two olefin-based polymers are at least two propylene-based polymers; a propylene-based polymer composition (A) including a propylene-based multistage polymer composed of the at least two kinds of propylene-based polymers, Further, the composition contains an ethylene-based polymer (B), the content of the propylene-based polymer composition (A) is 70% by mass to 98% by mass, and the content of the ethylene-based polymer (B) is 2% by mass to 30% by mass, based on 100% by mass of the total of the propylene-based polymer composition (A) and the ethylene-based polymer (B); Further, it contains 100 ppm to 10,000 ppm of a phosphate metal salt nucleating agent. film.
2. Satisfying the following formulas (1) and (2): The film of claim 1. (Nx×cosθ-Ny×cosθ) / d≧3.0×10 -8 ・・・(1) (!x!(!y!! / / / / d≧3EE!!!E\ that -8 ・・・() (In the formula, Nx represents the refractive index of the slow axis of the film determined by three-dimensional refractive index measurement. Ny represents the refractive index of the fast axis of the film determined by three-dimensional refractive index measurement. Nz indicates the refractive index in the thickness direction of the film determined by three-dimensional refractive index measurement. θ is the angle (°) between the MD direction of the film and the slow axis, determined by three-dimensional refractive index measurement. Shows. d indicates the thickness of the film (nm).
3. The propylene-based polymer composition (A), The content of the cold xylene soluble portion is 5 to 25 mass%, and the intrinsic viscosity [η] of the cold xylene soluble portion is CXS is 1.5 to 3.5 dL / g, The content of the cold xylene insoluble portion is 75 to 95 mass%, and the intrinsic viscosity [η] of the cold xylene insoluble portion is CXIS is 1.0 to 2.5 dL / g; The film according to claim 1 or 2.
4. The composition contains 5% by mass to 30% by mass of a propylene-based polymer composition (C) including a propylene-based multistage polymer composed of the at least two kinds of propylene-based polymers, The propylene polymer composition (C) satisfies the following formula (3): The film according to any one of claims 1 to 3. MT C >70×MFR C-1.1 ・・・(3) (In the formula, M.T. C indicates the melt tension (mN) measured at a temperature of 190° C. and a take-up speed of 15.7 m / min. MFR C indicates the melt flow rate (g / 10 min) measured at a temperature of 230° C. and a load of 2.16 kg.
5. A method for producing the film according to any one of claims 1 to 4, comprising the steps of: A melt-kneading step of melt-kneading a mixture containing at least two kinds of propylene-based polymers, an ethylene-based polymer, and a phosphate metal salt-based nucleating agent; an extrusion step of extruding the kneaded material obtained in the melt kneading step into a sheet shape; a cooling step in which the sheet-like kneaded material obtained in the extrusion step is pressed against a cooling roll by gas blown out of an air chamber to cool it; and forming a film by forming the sheet-like kneaded material into a film. In the cooling process, the amount of gas blown out of the air chamber is adjusted so that the gas pressure in the air chamber is 50 Pa to 300 Pa. A method for manufacturing a film.
Citation Information
Patent Citations
Propylene resin composition
JP1997316283A
Polypropylene-based sealant film and laminate using the same
JP2019172780A
Film and method for producing film
JP2021046471A
Sealant film and packaging material
WO2017098953A1